Analisis Perbedaan Pertumbuhan Zoysia japonica pada Penggunaan Naungan dan Pengaruh Pemberian Hormon Auksin dengan Media Tanam Pasir - Rahayu; Herawati, Aktavia; Suntoro; Nawangsari, Relly Yunila (Jurnal Lanskap Indonesia, 2025)
Soccer is one of the most popular sports in the world including Indonesia. However, the development of soccer in Indonesia has been delayed, one of the causes is the lack of soccer sports facilities. The management of soccer stadiums in Indonesia still pays little attention to proper treatment to grow turfgrass in accordance with international standards from FIFA. Another type of grass that can be used as an alternative to soccer stadium turfgrass in Indonesia is Japanese grass (Zoysia japonica), this type of grass is chosen because it has pointed leaves so it will not be quickly damaged by soccer shoe spool. Therefore, this study aims to determine the characteristics of Zoysia japonica with various management, especially on the use of shade and the effect of auxin hormone administration which can be used as a reference recommendation for improving grass quality and grass management suitable for soccer stadiums in Indonesia. This study used a Split Plot design with two factors. The results showed that the interaction of shade treatment and auxin hormone had a very significant effect on all observation parameters. In an environment with 70% shade, Zoysia japonica can still survive, but its growth will be better if given 100% auxin hormone.